PENANDA LINGUAL PADA RAGAM TUTURAN NASKAH KUNO TUNTUNAN MELAKUKAN HUBUNGAN SUAMI ISTRI - Wido Hartanto (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2019)
Ancient text is an important historical relic as it carries certain messages. The messages is the real proof and moral teaching of ancient time. Language used here has its own uniqueness, especially lingual sign and context that is related to directive speech. This research studies directive speech variety in ancient text Tuntunan dalam Melakukan Hubungan Suami-Istri (TDMHSI) which consists in the lingual sign and context. TDMHSI text has the code 07_01666 and is stored in the Banda Aceh Public Museum. Located in Sultan Alaidin Mahmudsyah street, Banda Aceh. This text consists of 36 pages. This research aims to reveal sign and context of the TDMHS’s directive speech. The method applied was observation and the technique used were editing and dictation. Observation method applied aims to analyzed speech types, lingual sign and context of the TDMHSI’s text compare to other texts. Editing technique is useful to provide text closely similiar to the real one. Dictation text is used by writing what was dictated by Malay-Arabic language expert. This technique is needed to match the editing result so that information is not overlapped. This research found that there are 5 directive speech, whic are: prohibition (14 data), ordering (13 data), sugesting (5 data), begging (4 data), and reminding (1 data). Other lingual sign found are in the form of suffix as the basic form of directive speech, and context used as the basic dterminant directive speech.